1990
DOI: 10.1007/bf03349666
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma associated ventricular tachycardia blocked with atenolol

Abstract: Ventricular tachycardia in patients with phenochromocytoma is rare. We report a patient with a norepinephrine-secreting extra-adrenal pheochromocytoma who had exercise induced ventricular tachycardia. Prior to diagnosis, the patient was treated with a selective beta 1 blocker, atenolol, which resulted in suppression of the dysrhythmia and amelioration of the hypertension. This is the first reported case of selective beta blockade suppressing ventricular tachycardia in a patient with a pheochromocytoma. Electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The incidence is likely to be low and possibly exacerbated by reversible catecholamine-induced HCM/DCM (533). Not only will conventional antagonism of catecholamine excess with alpha receptor blockers followed by beta blockade help control hypertension and reverse or prevent any further structural deterioration (534), but there is anecdotal evidence that it prevents recurrence of ventricular arrhythmia (535). Early definite surgical treatment of the pheochromocytoma should be a priority, especially in cases with documented life-threatening arrhythmias.…”
Section: Pheochromocytomamentioning
confidence: 99%
“…The incidence is likely to be low and possibly exacerbated by reversible catecholamine-induced HCM/DCM (533). Not only will conventional antagonism of catecholamine excess with alpha receptor blockers followed by beta blockade help control hypertension and reverse or prevent any further structural deterioration (534), but there is anecdotal evidence that it prevents recurrence of ventricular arrhythmia (535). Early definite surgical treatment of the pheochromocytoma should be a priority, especially in cases with documented life-threatening arrhythmias.…”
Section: Pheochromocytomamentioning
confidence: 99%
“…Although sinus tachycardia occurs most frequently, pheochromocytomas have been associated with a wide variety of arrhythmias, including supraventricular [34], nodal [35], broad complex [36], ventricular tachycardia [37][38][39], torsade de pointes [40], and Wolff-Parkinson-White syndrome [41]. Furthermore, atrial fibrillation [42] and ventricular fibrillation [5,43,44] have been reported.…”
Section: Arrhythmiamentioning
confidence: 99%
“…In case of atrial fibrillation or flutter, the cardioselective β 1‐blocker esmolol can be given intravenously, provided adequate α ‐blockade has been ensured [52]. Lidocaine or atenolol have been used with success for ventricular arrhythmias [52, 53].…”
Section: Emergency Treatment Of Pheochromocytomamentioning
confidence: 99%